Adaptive Leadership of School Principals in Improving Teacher Performance in the Archipelago: A Qualitative Study on State Junior High Schools in Simeulue Regency - Astuti, Dewi; Ismail, Ismail; Rasyid, Suparta; Intan Puspita, Gusti (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
​ ​Objective: This study aimed to analyze how school principals apply adaptive leadership to improve teacher performance in archipelagic areas with limited educational resources. This study aimed to identify adaptive leadership patterns that emerge in various geographical contexts and examine their influence on teacher motivation, professionalism, and work culture in junior high schools in Simeulue Regency, Aceh Province, Indonesia. Methods: This study used a descriptive qualitative approach involving three state junior high schools: SMPN 1 Simeulue Tengah, SMPN 1 Simeulue Timur, and SMPN 2 Teupah Barat. Data were collected through semi-structured interviews, participatory observations, and documentation studies of nine informants, comprising three principals and six teachers. Data analysis was carried out with an interactive model that included data reduction, data presentation, and conclusion drawing, and was validated through triangulation of sources and methods to ensure the validity of the findings. Results: The results of the study show that the adaptive leadership of school principals is manifested in four main contextual styles: transformational, democratic, participatory, and spiritual. Transformational leadership dominates the central region, democratic leadership the coastal region, and participatory-spiritual leadership the outer island region. Adaptive leadership has been proven to increase motivation, professionalism, and cohesion of teachers' work culture through innovation, collaboration, and moral commitment, even in the midst of limited facilities and administrative burden. Novelty: This study integrates spiritual and socio-cultural values within the framework of adaptive leadership, resulting in a contextual adaptive leadership model relevant to schools in the archipelago. These findings expand adaptive leadership theory by emphasizing humanistic and value-based dimensions in the context of Indonesian education.​